Copper requirements of broiler breeder hens. (11th July 2018) - Berwanger, E; Vieira, S L; Angel, C R; Kindlein, L; Mayer, A N; Ebbing, M A; Lopes, M
Abstract: One-hundred-twenty Cobb 500 hens, 20 wk of age, were randomly allocated into individual cages with the objective of estimating Cu requirements. After being fed a Cu deficient diet for 4 wk, hens were fed diets with graded increments of supplemental Cu (0.0; 3.5; 7.0; 10.5; 14; and 17.5 ppm) from Cu sulfate (CuSO4 5H2 O), totaling 2.67; 5.82; 9.38; 12.92; 16.83; and 20.19 ppm analyzed Cu in feeds for 20 weeks. Estimations of Cu requirements were done using exponential asymptotic (EA), broken line quadratic (BLQ), and quadratic polynomial (QP) models. Obtained Cu requirements for hen d egg production and total settable eggs per hen were 6.2, 7.3, and 12.9 ppm and 8.1, 9.0, and 13.4 ppm, respectively, using EA, BLQ, and QP models. The QP model was the only one having a fit for total eggs per hen with 13.1 ppm Cu as a requirement. Hemoglobin, hematocrit, and serum Cu from hens had requirements estimated as 13.9, 11.3, and 18.5,  ppm; 14.6, 13.0, and 19.0 ppm; and 16.2, 14.6, and 14.2 ppm, respectively, for EA, BLQ, and QP models. Hatching chick hemoglobin was not affected by dietary Cu, whereas requirements estimated for hatching chick hematocrit and body weight and length were 10.2, 12.3, and 13.3 ppm using EA, BLQ, and QP models; and 6.8 and 7.1 ppm, and 12.9 and 13.9 ppm Cu using EA and BLQ models, respectively. Maximum responses for egg weight, yolk Cu content, and eggshell membrane thickness were 14.9, 12.7, and 15.1 ppm; 15.0, 16.3, and 15.7 ppm; and 7.3, 7.8, and 14.0 ppm Cu, respectively, for EA, BLQ, and QP models. Yolk and albumen percentage were adjusted only with the QP model and had requirements estimated at 11.0 ppm and 11.3 ppm, respectively, whereas eggshell mammillary layer was maximized with 10.6, 10.1, and 14.4 ppm Cu using EA, BLQ, and QP models, respectively. The average of all Cu requirement estimates obtained in the present study was 12.5 ppm Cu.